If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -39 = 7x + 61 Reorder the terms: -39 + 2x = 7x + 61 Reorder the terms: -39 + 2x = 61 + 7x Solving -39 + 2x = 61 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -39 + 2x + -7x = 61 + 7x + -7x Combine like terms: 2x + -7x = -5x -39 + -5x = 61 + 7x + -7x Combine like terms: 7x + -7x = 0 -39 + -5x = 61 + 0 -39 + -5x = 61 Add '39' to each side of the equation. -39 + 39 + -5x = 61 + 39 Combine like terms: -39 + 39 = 0 0 + -5x = 61 + 39 -5x = 61 + 39 Combine like terms: 61 + 39 = 100 -5x = 100 Divide each side by '-5'. x = -20 Simplifying x = -20
| w+10=0 | | 10x-1+17x+3+97=180 | | 7(x+3)=(7x+21) | | -5x-115=67-12x | | 2a-3(4a+5)=-6(a-3)-1 | | 4x+15=34 | | -4(3-5x)=8 | | 7(2-3x)=5x | | x^2-4x+-14=0 | | 27.2m+15.7=-85.94+.8m | | 22.2m+15.7=-85.94+.8m | | 3(5X+2)=6 | | 22.2m+15.7=85.94+.8m | | -8y-5+3y=7+4y-9 | | 3(a-4)=7a-4 | | 20-3t=6t-8*2 | | 8z-2(2-z)=2 | | -x+7=15 | | x*10=110 | | 14-6b+7-2b=1+5b | | 5-(2x-1)=x | | 3I+4=4I-3 | | 4(x+3)-1=7 | | -4(w+5)+9=-31 | | 5(m-5)+5=40 | | n+9=3n+5*5 | | -12x+8y=36 | | 35.84=27.02+294.9*x-373.7x | | -1(2n+3)=2(-4-7) | | 20-2(2w+1)=5w-2(5+w) | | 0*3+4=0*2+3 | | n+9=3n+5*4 |